Association between SARS-CoV-2 Seropositivity and Severity of Out-of-Hospital Acute Ischemic Stroke Following Asymptomatic/Mild COVID-19 in Children - Abdelkreem, Elsayed; Mahmoud, Ekram A.; Mohamed, Nesma A.; Abd-Elrehim, Ghada A. B.; Fahmy, Eman M. (Journal of Pediatric Infectious Diseases, 2023)
Objective This article investigates the frequency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seropositivity and its association with the severity of new-onset acute ischemic stroke (AIS) among previously healthy children with asymptomatic/mild coronavirus disease 2019 (COVID-19).Methods A case–control study that included children < 18 years with out-of-hospital AIS of undetermined etiology and a control group of healthy children. Exclusion criteria were current respiratory symptoms, previous COVID-19 diagnosis, prior COVID-19 vaccination, active SARS-CoV-2 infection, history of hospital admission in the last 6 months, and having a stroke predisposition. We screened children for SARS-CoV-2 immunoglobulin G antibodies using enzyme-linked immunosorbent assay. The severity of stroke was evaluated using the Pediatric National Institutes of Health Stroke Scale (PedNIHSS).Results The current study included 25 children (15 males and 10 females; median age 24 months) with out-of-hospital AIS and 25 healthy controls (11 males and 14 females; median age 24 months). SARS-CoV-2 seropositivity was detected in 15 (60%) of AIS children and 11 (44%) among controls (p = 0.258). Compared with seronegative AIS children, those seropositive for SARS-CoV-2 had higher PedNIHSS scores (median 19 vs. 8.5; p = 0.001), pediatric intensive care unit admission (93.3% vs. 40%; p = 0.007), need for mechanical ventilation (53.3% vs. 10%; p = 0.040), and D-dimer levels (median 3.5 vs. 1.75 μg/mL; p < 0.001).Conclusion SARS-CoV-2 seropositivity may be associated with more severe AIS affecting previously healthy children during the postacute phase of asymptomatic/mildly symptomatic COVID-19.
Keywords: SARS-CoV-2; COVID-19; stroke; children; serology